Pre-clinical xenotransplantation: physiology and pharmacy in human decedent and non-human primate models - Anderson, Douglas J.; Locke, Jayme E. (Frontiers in Transplantation, 2025)
Non-human primates and decedent humans have emerged as the two principal translational models in xenotransplantation. Each model has differing advantages and drawbacks. In this manuscript, we will compare and contrast the relative strengths of each model, focusing on the physiologic function of the xenograft in a human decedent or non-human primate. Additionally, we will discuss the pharmacologic agents typically employed in each model, highlighting both the ability of the decedent model to test clinically-relevant medication strategies that may be impossible in non-human primates due to species-specificity.